Exploring the characteristics of detrusor after contraction in females with pure urodynamic stress incontinence - Xiao Zeng; Hong Shen; Deyi Luo; Tao Jin (BMC Urology)
Abstract Purpose This study aims to evaluate detrusor after contraction (DAC) characteristics in females with pure urodynamic stress incontinence (USI). Methods We examined the urodynamics database from our urodynamic study center. Urodynamic data from pure USI cases with and without DAC were compared. DAC was categorized based on morphological features, and urodynamic parameters in different subgroups were analyzed. Results A total of 61 female pure USI patients met all the study requirements. Among them, there were 27 cases of pure USI with DAC and 34 cases of pure USI without DAC. The incidence of pure USI with DAC in the overall female sample was 2.5%.Significant differences were observed in Qmax between pure USI with DAC and pure USI without DAC (20.1 ± 7.2 vs. 13.0 ± 6.8, p = 0.00), as well as in Pdetqmax (24.3 ± 15.1 vs. 16.3 ± 9.8, p = 0.02). Comparing parameters among the three subtypes of DAC revealed statistical differences in uroflow time: Type 1 DAC vs. Type 2 DAC vs. Type 3 DAC [21(20,22.5) vs. 22(16,27) vs. 30(26.8,30.8), p = 0.02], and in the maximum DAC contraction amplitude [64(46.5,107) vs. 39(25.5,48) vs. 45.5(24,74.8), p = 0.03]. Additionally, DAC was categorized into three subgroups: Type 1, Type 2, and Type 3. Conclusions This study offers an initial exploration of morphological and mathematical aspects of DAC in urodynamics involving females with pure USI. The findings also suggest DAC may serve as a potential new indictor of bladder function in females with pure USI. Trial registration Not applicable.